Novice Nurses’ Experiences Caring for Acutely Ill Patients during a Pandemic - Naylor, Heather; Hadenfeldt, Cynthia; Timmons, Patricia (Nursing reports (Pavia, Italy), 2021)
The Coronavirus pandemic erupted in 2020 and new graduate registered nurses (RNs) found themselves caring for those with devastating illness as they were transitioning into nursing practice. The purpose of this study was to describe the experience of novice nurses working in acute care settings during a pandemic. This qualitative phenomenological study of novice nurses working in facilities providing acute care for COVID-19 patients was conducted in Phoenix, Arizona, USA. Purposive sampling identified 13 participants for interviews. Data were analyzed using thematic analysis. Eight themes emerged: Dealing with death, Which personal protective equipment (PPE) will keep us safe?, Caring for high acuity patients with limited training, Difficulties working short-staffed, Everything is not okay, Support from the healthcare team, Nursing school preparation for a pandemic, I would still choose nursing. Novice nurses felt challenged by the experience and were at times overwhelmed and struggling to cope. Support from peers and coping skills learned during nursing school helped them continue to work during a critical time. Data from this study suggest that some participants may have been experiencing symptoms of anxiety, depression, or post-traumatic stress disorder, and findings provide foundational insights for nursing education and psychological interventions to support the nursing workforce.